2011
DOI: 10.1111/j.1528-1167.2011.03056.x
|View full text |Cite
|
Sign up to set email alerts
|

Second-line status epilepticus treatment: Comparison of phenytoin, valproate, and levetiracetam

Abstract: SUMMARYPurpose: Phenytoin (PHT), valproic acid (VPA), or levetiracetam (LEV) are commonly used as second-line treatment of status epilepticus (SE), but comparative studies are not available. Methods: Among 279 adult SE episodes identified prospectively in our tertiary care hospital over 4 years, we retrospectively identified 187 episodes in which PHT, VPA, or LEV were given after benzodiazepines. Patients with postanoxic SE were not included. Demographics, clinical SE features, failure of second-line treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
5
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 30 publications
7
101
5
4
Order By: Relevance
“…Class III trials support efficacy and safety of valproic acid as first-line therapy (26,27), second-line therapy (31,32), and refractory therapy (66). Evidence for use of levetiracetam and lacosamide is limited to retrospective studies (67)(68)(69)(70)(71)(72). Given the favorable pharmacokinetic characteristics and adverse-effect profiles for these medications compared with fosphenytoin and phenobarbital, comparative trials of these medications as second-line therapy will provide vital evidence to improve future treatment of convulsive status epilepticus.…”
Section: Future Directionsmentioning
confidence: 99%
“…Class III trials support efficacy and safety of valproic acid as first-line therapy (26,27), second-line therapy (31,32), and refractory therapy (66). Evidence for use of levetiracetam and lacosamide is limited to retrospective studies (67)(68)(69)(70)(71)(72). Given the favorable pharmacokinetic characteristics and adverse-effect profiles for these medications compared with fosphenytoin and phenobarbital, comparative trials of these medications as second-line therapy will provide vital evidence to improve future treatment of convulsive status epilepticus.…”
Section: Future Directionsmentioning
confidence: 99%
“…The clinical data on efficacy and order of intravenous LEV in SE are still controversial. Alvarez et al (2011) reported that intravenous LEV was not as effective as sodium valproate for seizure control in SE after benzodiazepine treatment. In contrast, G谩mez-Leyva et al (2009) showed that intravenous LEV had potential effectiveness for SE treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of publications until 2009 reported that 707 patients with various forms of SE had been safely treated with LEV, with a success rate was about 70% (3). In ESE, the efficacy of LEV was reported as 51.7% in one study (23) and 73.2% in another study (21). VPA has been used for the treatment of SE in prospective or retrospective series and two randomized open trials (12).…”
Section: Minutes) It Is a Condition Which Can Have Long-term Conseqmentioning
confidence: 99%
“…SE did not respond to 25.4% of cases treated with VPA, 41.4% treated with FOS, and 48.3% treated with LEV (23). Importantly, this was an open, nonrandomized trial, and the severity of SE in VPA treated patients may have been less than the other two groups, which may explain part of the apparent superiority of VPA in the study (23). Two ESE treatment studies were open, randomized, prospective studies.…”
Section: Minutes) It Is a Condition Which Can Have Long-term Conseqmentioning
confidence: 99%